Shaking table test on seismic performances of newly designed joints for mountain tunnels crossing faults. Issue 2 (January 2020) - Yan, Gaoming; Gao, Bo; Shen, Yusheng; Zheng, Qing; Fan, Kaixiang; Huang, Haifeng
The zones where tunnels pass through faults are considered to be severely damaged during earthquakes. Site investigation of tunnels crossing faults revealed that there were different types of damage patterns after earthquakes. This article proposed a new seismic design concept of "guiding" and "yielding." Two types of joints, multilevel brittle-flexible joint and flexible joint, were based on this concept and were investigated in this study. A series of shaking table tests were conducted on reduced scale tunnel models under two steps of the loading process, fault movement and subsequent seismic excitation with increasing intensities. The results showed that both types of joints clearly reduced the seismic responses of the tunnel lining. The idealized behavior—step-like deformation—appeared along the longitudinal direction of the tunnel in the two tests. No shear failure of the tunnel linings was found, and the longitudinal cracks in the crown, arch springing, and invert were common in the tests. The multilevel brittle-flexible joint was verified to be more appropriate for tunnels subject to massive earthquakes.